PEMBINAAN AKHLAK DALAM ISLAM - Muhrin, Muhrin (EDUCATIONAL JOURNAL : General and Specific Research, 2025)
Moral development is an educational or development process that aims to shape and improve an individual's behavior, morality and ethical values ​​so that they conform to the moral standards recognized in a particular culture or ethical system. Moral development is an important part in the formation of a society that behaves well and justly and is an integral aspect in many ethical, religious and philosophical systems. It aims to create individuals who are able to make wise decisions, act with integrity, and contribute positively to society. In Islam, moral development is very much needed, especially nowadays, many people have deviated from Islamic teachings. Therefore, moral development must be instilled as early as possible so that a person's moral character is inherent in him. Noble morals will make people happy in their lives, and vice versa. In another sense, moral development in Islam does not conflict with each other but complements each other, namely traits that are deeply embedded in the soul which appear in outward actions that are carried out easily, without requiring any further thought and have become a habit.